2020
DOI: 10.1108/bfj-12-2019-0914
|View full text |Cite
|
Sign up to set email alerts
|

UK consumers' willingness to pay for laying hen welfare

Abstract: PurposeThis study investigates UK consumers’ perception and willingness to pay (WTP) for egg attributes associated with laying hen welfare, namely with beak-trimming practices and injurious feather pecking (IP). The aim is to examine any change in WTP after improved consumer awareness.Design/methodology/approachBuilding upon existing literature, the authors designed an online survey in which the method of discrete choice experiment (DCE) was employed. The study includes two identical DCEs with the second being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Summing up all these findings, it shows that a higher level of evangelism for the brand and good environmental knowledge results in a high level of ecological buying behaviour in consumers, especially in dealing with eatable products. The results are coherently consistent with the existing literature (Badrinarayanan & Sierra, 2018;Li, et al, 2020;Dunne & Siettou, 2020), whereas some identified gaps are also bridged by the present findings (Sun, Su, Guo, & Tian, 2021; Musa, Mansor, & Musa, 2020; Karunarathna, Bandara, Silva, & De Mel, 2020). These findings direct practitioners to move from traditional marketing tactics towards novel covert or overt marketing techniques.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Summing up all these findings, it shows that a higher level of evangelism for the brand and good environmental knowledge results in a high level of ecological buying behaviour in consumers, especially in dealing with eatable products. The results are coherently consistent with the existing literature (Badrinarayanan & Sierra, 2018;Li, et al, 2020;Dunne & Siettou, 2020), whereas some identified gaps are also bridged by the present findings (Sun, Su, Guo, & Tian, 2021; Musa, Mansor, & Musa, 2020; Karunarathna, Bandara, Silva, & De Mel, 2020). These findings direct practitioners to move from traditional marketing tactics towards novel covert or overt marketing techniques.…”
Section: Discussionsupporting
confidence: 93%
“…Literature also explored well that environmental knowledge and being conscious in human actions are the factors for behaviour building (Goh & Balaji, 2016). Similarly, a study in the context of UK consumers assures the significant consideration of environmental factors in their mindset, especially while paying for eatable products (Dunne & Siettou, 2020). Under the pandemic situation and increasing trends in environmental consideration, customers had developed a positive attitude toward reducing the adverse environmental effect of their product buying and consumption (Cheung & To, 2019; Chen, Hung, Wang, Huang, & Liao, 2017).…”
Section: Moderation Of Brand Evangelism Habitat Attitude and Environm...mentioning
confidence: 99%
“…First, compared to the self-declared claim "export quality", consumers prefer the Santong claim. Previous studies have indicated that consumers pay attention to food products with production claims, including production systems, production methods and processing methods [60][61][62][63][64]. Asante-Addo and Weible [65] reported that consumer utility increases when an antibiotic/hormone-free claim is made for a meat product.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, previous studies indicated higher consumers’ WTP for food health, safety and nutrition concerns (e.g. Talwar, 2021; Dunne and Siettou, 2020; Konuk, 2018). Moreover, as packaging plays a crucial role in linking food quality and consumers through its functions such as communication, conservation and preservation, an increasing number of consumers are willing to pay a premium for eco-friendly packaged products.…”
Section: Theoretical Frameworkmentioning
confidence: 99%